Methods for the determination of metals and inorganic chemicals in environmental samples (Noyes Publications, 1996)
Part I is a supplement to the EMSL-Cincinnati publication "Methods for the Determination of Metals in Environmental Samples" and was prepared to revise and place in the Environmental Monitoring Management Council (EMMC) format certain spectrochemical methods used for metals. Part II, the EMSL-Cincinnati publication "Methods for the Determination of Inorganic Substances in Environmental Samples" was prepared as the continuation of an initiative to gather together a compendium of standardized laboratory analytical methods